O jornalismo como uma arma de combate: uma análise dos perfis de reportagem da Rede Globo na cobertura da tematização do racismo no esporte - Esteves, Emerson Maciel (2023)
Issues relating to ethnic-racial conflicts are gaining more and more space in the media, communication and more specifically in journalism. In sport, due to the Annual Reports of the Football Racial Discrimination Observatory, sports journalists have a reliable source of information to assess racism in sport. Journalism and journalists have been increasingly challenged to deal with the topic. Some authors point out the need to think about journalism and Communication in a combative and pedagogical way. Journalism can serve as an institution of knowledge and education to break stereotypes in society. But, in practice, how has sports television journalism worked? In a context of the outbreak of racial protests, the general objective of this research is to reflect the journalism profiles that can be identified in Rede Globo's coverage regarding ethnic-racial conflicts in sport. Is it possible to say that there is activism in the coverage or is there a prevalence of objectivity? The methodological approach of the research corresponds to content analysis and case study, the corpus of analysis are the reports that address the theme of ethnicracial conflicts available on the Globoplay platform between 2017-2021. Data analysis pointed to a profile that predominates the fight against racism within the reports. However, this approach prevails in the space of national and weekly journalism. However, there was a predominance of this profile in national and weekly journalism. In regional and daily journalism, detachment and objectivity prevailed. At the end of the study, it was possible to characterize an activist reporting formula within Telejournalism with regard to sports coverage.